Inextensible curves in the Galilean space - Ogrenmis, Alper Osman; Yeneroglu, Mustafa (Academic Journals, 2010)
In this paper, we investigated inextensible flow of curves in Galilean space. Conditions for an inextensible curve flow were expressed as a partial differential equation involving the curvature and torsion.
Keywords: Galilean space; inextensible curves; Frenet formulas